PENGARUH GAYA HIDUP, SIKAP UANG, NILAI PRIBADI, STIMULASI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN TERHADAP SMARTPHONE ANDROID (Studi Kasus Mahasiswa Muhammadiyah Stikes Banjarmasin) - Arina Putri; Nuril Huda (Universitas Lambung Mangkurat, 2018)
This study aims to identify and analyze the influence of lifestyle variables (X1), money attitude (X2), personal values (X3), marketing stimulation (X4) on purchase decisions (Y). Methods This study uses qualitative research by distributing questionnaires to students stikes muhammadiyah Banjarmasin ever using smartphones as much as 157 respondents. Using variable measurement technique kiteria interval scale from strongly agree to strongly disagree, with weights from 1 - 10. To determine the effect of variable X to variable Y using multiple linear regression analysis technique. Results of this study conclude that (1) There is a significant difference between lifestyle variables to variable purchase decision. (2) There is a significant relationship between the variables attitude toward money purchase decision variables. (3) There is a significant relationship between the variables of personal values to the variable purchase decision. (4) There is no significant relationship between the variables of marketing stimulation to variable purchase decision.